2016
DOI: 10.1097/01.epx.0000484091.57255.c0
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus in patients on regular hemodialysis in Beni-Suef Governorate, Egypt

Abstract: HCV infection still remains a predominant problem among patients on maintenance HD in Beni- Suef governorate History of blood transfusion and history of shistosomiasis were significant risk factors for acquiring HCV infection in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
1
5
0
1
Order By: Relevance
“…The results are agreement with a previous studies have reported in Iraq [26], and in Iran [27]. But they were disagreement with the other study in Egypt [28]. Also, there were not significant differences (p >0.05) between sex and anti-HCV positive in the study, this similar to another previously reported study [29].…”
Section: Discussionsupporting
confidence: 72%
“…The results are agreement with a previous studies have reported in Iraq [26], and in Iran [27]. But they were disagreement with the other study in Egypt [28]. Also, there were not significant differences (p >0.05) between sex and anti-HCV positive in the study, this similar to another previously reported study [29].…”
Section: Discussionsupporting
confidence: 72%
“…The minimum prevalence was 0.8% (Libya) [ 25 ] and 2.3% (Nigeria) [ 23 ] for HBV and HCV, respectively. On the other hand, the maximum prevalence of HBV and HCV was 60.7% (Egypt) [ 59 ] and 60.9% (Egypt) [ 43 ], respectively. A total of 23 studies reported the prevalence of HBV in HD patients.…”
Section: Resultsmentioning
confidence: 99%
“…Plusieurs études, s'étaient intéressées à sa prévalence en hémodialyse, et cette dernière diffère selon les pays et les centres d'hémodialyse. Senosy SA et al [15] rapportaient une prévalence de 60,9% dans un centre de dialyse en Egypte, tans disque Hasanjani R et al [16], en Iran, rapportaient dans leur etude une prévalence à 8,7% de patients infectés par le VHC. Cette prévalence de l'infection par le VHC parmi nos populations dialysées constitue une véritable menace de santé publique, car en plus de sa transmission par voie sanguine, il se transmet également par voie sexuelle.…”
Section: Discussionunclassified